2020
DOI: 10.1108/lodj-03-2019-0127
|View full text |Cite
|
Sign up to set email alerts
|

Promoting firm innovativeness through servant leadership and corporate social responsibility to employees

Abstract: PurposeBased on the upper echelons and organisational identification theories, this paper focuses on the relationship between servant leadership and firm innovativeness, as well as the underlying mechanisms that explain this relationship. More specifically, we analyse the relationship between servant leadership, firm innovativeness and corporate social responsibility to employees (CSRE).Design/methodology/approachA total of 285 Spanish firms took part in the study, and 570 questionnaires were gathered. Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 81 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…Moreover, Ratajczak and Szutowski [75] also confirmed that an organization's CSR activities are directly related to employee's innovation performance. Several other scholars also hold the same argument that CSR is positively related to EIB [76][77][78][79].…”
Section: Theory and Hypothesesmentioning
confidence: 79%
“…Moreover, Ratajczak and Szutowski [75] also confirmed that an organization's CSR activities are directly related to employee's innovation performance. Several other scholars also hold the same argument that CSR is positively related to EIB [76][77][78][79].…”
Section: Theory and Hypothesesmentioning
confidence: 79%
“…When the leadership is developing a good strategy for sustainable development, a consistent commitment to sustainability within the organization is required (Lee and Schaltegger, 2014 ). Leadership plays an important role in promoting CSR (Fenwick, 2007 ; Mayo et al, 2016 ; Mallén Broch et al, 2020 ; Nguyen et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Upper echelon theory states that top managers’ values and cognition have a great impact on their perception of the environment, which, in turn, affects firms’ strategic decisions and performance ( Hambrick and Mason, 1984 ). Researchers have applied upper echelons theory to analyze the effects of different types of CEO leadership on firm outcomes ( Zhang et al, 2015 ; Mallen Broch et al, 2020 ). However, upper echelons research has often been criticized for not exploring the “black box” between CEO characteristics and distal firm outcomes ( Neely Lovelace et al, 2020 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%